The Effect of Using Ice Breaking “Recognize My Voice” on Strengthening the Collaboration Skills of Grade 3 Students of Sdn 2 Karyajaya Rangkasbitung - Heryansyah, Muhamad Rifky; Supriatna, Encep (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
The study aims to analyze the effect of using Ice Breaking "Recognize My Voice". Towards strengthening the cooperation skills of Grade 3 Students of SDN 2 Karyajaya Rangkasbitung. By using a Quantitative research method with a pretest - posttest design. Using the research subjects were grade 3 students of SDN 2 Karyajaya Rangkasbitung who were selected by purposive sampling. The results of the study indicate that the use of Ice Breaking "Recognize My Voice" can improve students' cooperation skills. Based on the results of the pretest and posttest data analysis, there was a significant increase in aspects of communication, responsibility, and teamwork. This study found that there were indications that interactive and fun ice breaking activities were effective in improving group dynamics and strengthening cooperation skills in the learning environment. This study can provide implications for the application of ice breaking methods that are in line, so that they can be an alternative strategy for teachers in creating or creating a collaborative learning atmosphere.
Keywords: ice breaking; cooperation skills; elementary school student